Simultaneous wastewater treatment and power generation with single chambered up-flow membrane-less microbial fuel cell / \c Thung Wei Eng. - Thung, Wei Eng (School of Environmental Engineering, Universiti Malaysia Perlis, 2018)
The overall aim of this research is to develop a single chamber membrane-less MFC for wastewater treatment. A distinctive design of MFC is necessary to overcome the typical limitations before for real application.The distinctive designed MFC is expected not only to improve the performance of wastewater treatment, but also to enhance the electricity generation at low fabrication and operation costs. Therefore, the major focus of thisproject is to develop and investigate the mechanism of the low cost distinctive MFC forsimultaneous dye wastewater treatment andelectricity generation.The mainobjectives of this research are to ; design and develop single chambered up-flow membrane-less MFCs under batch and continuous mode for simultaneous wastewater treatment and electricity generation ; evaluate and enhance the performance of MFC with various parameters: Cathode material, electrode spacing, organic loading rate, ionic strength, dye concentration, and etc ; explore the mechanisms and degradation pathway during AO7 decolorization insingle chambered up-flow membrane-less MFC ; inspect the performance of enhanced scaled-up up-flow membrane-less MFC by various anode configuration.